Effect of alkaline activator properties on the fly ash based geopolymer concrete for ambient curing condition - Nath, Pradip; Sarker, Prabir (Concrete Institute of Australia, 2013)
Geopolymer is synthesized by activating alumino-silicate materials with an alkaline activator. The curing temperature has a significant effect on the setting and strength gain of geopolymers and curing is usually done at an elevated temperature. In addition to the curing temperature, the properties of geopolymer mixture are influenced by the type, chemical compositions and doses of alkaline activator solutions. The aim of this study is to investigate the effect of various mixture parameters of alkaline activator solution on the properties of fly ash based geopolymer mixture produced in ambient curing condition. Class F fly ash was used to prepare geopolymer mortars. Ordinary Portland cement was added as an additive with fly ash to enhance the early age properties of concrete in ambient curing condition (about 23oC and RH 60±10%). Fly ash was activated by a mixture of sodium silicate (SS) solution and sodium hydroxide (SH) solution. Three different types of SS were mixed with SH in different ratios (SS/SH = 1.5, 2.0, 2.5). The results indicate that, setting time and compressive strength of the OPC blended fly ash geopolymer mixture vary with the variation of chemical composition of alkaline activator solution. The critical molar ratios of geopolymer mixture were correlated with the properties of the mixtures. Generally, strength increased with the increase of Na2O/SiO2 and decrease of H2O/Na2O ratio.